Impact of e-commerce on the performance of agroexports in the central region of Peru - Gamarra Curo, Yeny (2020)
The objective of the research was to determine the impact of electronic commerce on the performance of agroexports in the central region of Peru, 2020. The study was carried out from a quantitative approach with a nonexperimental - cross-sectional - causally correlated research design. Using the survey technique, two questionnaires were applied to 95 agro-exporters, one for electronic commerce and the other for export performance. Using the structural equations model, it was obtained that electronic commerce in its compatibility dimension does not have a positive impact on the efficiency of the distribution of companies (p > 0.05) and does have a positive impact on the efficiency of communication (p < 0.05). Regarding ease of use, it does not have a positive impact on the efficiency of the distribution (p > 0.05; however, it does have a positive impact on the efficiency of communication (p < 0.05). Regarding the perceived utility it has a positive impact on the efficiency of distribution (p < 0.05), but it does not have a positive impact on the efficiency of communication. It is concluded that the compatibility and ease of use of electronic commerce positively impact the performance of communication efficiency in agro-exports and the perceived utility has a positive impact on the performance of the efficiency of distribution in agro-exports of the companies of the central region of Peru